Methylation profile of individuals with sickle cell trait - Vasconcelos, Ana Gabriela; Johnson, Mari; Cai, Yanwei; Hsu, Li; Franceschini, Nora; Auer, Paul L.; Kooperberg, Charles; Raffield, Laura M.; Reiner, Alex P. (Epigenetics, 2025)
Sickle cell trait (SCT) is due to heterozygosity for the β-globin sickle cell mutation. SCT recently has been associated with increased risk of various adverse health outcomes. DNA methylation (DNAm) is one potential mechanism by which SCT may impact disease risk. To identify DNAm sites associated with SCT, we conducted an epigenome-wide association (EWAS) meta-analysis using whole blood Illumina EPIC array data available in a total of 3,677 African American participants (including 1,071 with SCT) from the Women's Health Initiative and Jackson Heart Study. We identified 103 differentially methylated CpGs and 119 differentially methylated regions associated with SCT. The strongest signals were hypermethylated cis loci within predicted regulatory elements within or near the β-globin gene cluster on chromosome 11. Beyond the globin locus, SCT-associated DMPs were enriched in genes involved in redox regulation and oxidative stress. We also demonstrate an association of SCT with differences in biological age and epigenetic age acceleration, though the pattern and strength of association differ according to the epigenetic clock used. Specifically, more recent epigenetic clocks that incorporate clinical phenotypes or laboratory biomarkers related to adverse health outcomes are associated with accelerated aging among individuals with SCT compared to African American controls. Our results lay the groundwork for future study of the role of DNAm in biologic aging and related health outcomes among individuals with SCT.